Clinical Parameters Predicting Survival Duration after Hepatectomy for Intrahepatic Cholangiocarcinoma - Bei-ge Jiang; Rui-liang Ge; Liang-liang Sun; Ming Zong; Gong-tian Wei; Yong-jie Zhang (Canadian Journal of Gastroenterology)
BACKGROUND: Currently, the most effective treatment for intrahepatic cholangiocarcinoma (ICC) is complete hepatic tumour excision.